USER ATTITUDE TOWARDS PREFERENCE OF E-LEARNING IN BANGLADESH - Chowdhury, Mustafa Manir; Islam, Md. Shahidul; Rahman, Mohammad Toufiqur; Akter, Kulsuma; Shahabuddin, A. M. (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
Information and Communication Technology (ICT) is crucial in facilitating the teaching and learning process in the current educational setting during COVID-19. In this context, the global demand for the integration of ICT in Education has rapidly increased. During the COVID-19 pandemic, e-learning gained widespread popularity as people remained indoors for health and safety reasons. This situation led to a rapid increase in positive attitudes toward e-learning. This study investigates the factors influencing students' attitudes toward e-learning and examines whether this Attitude impacts their Preference for e-learning. Utilizing survey data from 400 respondents collected between January and March 2024, this research employs a purposive sampling approach with questionnaires measuring awareness of e-learning, e-learning education facilities, benefits, costs, attitudes, and preferences, all on a five-point Likert scale. Factor analysis categorizes the data into six factors, which are then validated using Cronbach's alpha in IBM SPSS Statistics 26. A structural equation model (SEM) is developed in IBM SPSS AMOS 22 to analyze the Preference for e-learning education based on attitudes and their associated factors, further validated through convergent and discriminant validity. The results reveal that e-learning facilities and benefits positively influence attitudes towards e-learning, while the Cost of e-learning negatively impacts these attitudes. However, awareness of e-learning only significantly affects attitudes. A positive attitude towards e-learning significantly enhances the Preference for e-learning education. The findings of this study highlight the critical role of perceived benefits and cost considerations in shaping student attitudes and preferences for e-learning education.JEL Classification Codes: D83.